Mammal utilisation of artificial water sources in the central Kruger National Park: contemporary seasonal patterns and implications for climate change scenarios - Trent, Amy Jean (My University, 2016)
Monitoring the status and abundance of mammals, as well as establishing threats to biodiversity in different areas, is an essential management requirement in protected areas. Monitoring mammal species can assist in determining species interactions, patterns of behaviour and is important for further research, policy and management strategies. Water provision has implications for the preservation of wildlife, and is thus a management concern. Numerous studies monitoring mammal water utilisation patterns have employed traditional data collection methods, which are restricted primarily to diurnal observation during specific time intervals. Given the projected future impacts of global climate change on regional water availability, it is essential to investigate current water usage by mammals in the Kruger National Park (KNP), so as to better ascertain likely future water requirements under climate change scenarios. The use of remote photography for scientific observation, investigation and monitoring has many potential benefits, and an innovative and relatively new method through which one can observe mammal water source visitation patterns, is through the use webcams. There has been comparatively little research on mammal water requirements and visitation patterns at water provisioning sites using remote photography as a data collection method. Further to this, there is a gap in our knowledge concerning how daily climate variables (viz. temperature and rainfall) and astronomical conditions control water source visitation patterns at the finer temporal scale. This research primarily contributes to understanding contemporary water source visitation patterns and how this will influence future management decisions. At a broader scale, determining recent visitation patterns is critical in the context of projected future climatic changes and the associated water requirements for mammals of KNP. Webcam images were obtained for the period March 2012 - March 2014, captured at two artificial water sources in the central KNP. A clear divide is exhibited between herbivore and carnivore visitation patterns, with herbivores exhibiting exclusively diurnal patterns and carnivores’ nocturnal patterns. Significant relationships with Tavg intervals demonstrate that the majority of herbivores are shifting their visitation periods earlier in the day per 5°C increase in mean daily temperature, while the majority of carnivores are shifting their visitation periods later in the night per 5°C increase in mean daily temperature, however there is variability of species responses across the two study sites. Under the highest Tavg interval (30°C - 35°C) impala, warthog, southern giraffe, African buffalo and plains zebra exhibit a shift to earlier visitation by 1 – 6 hours, forcing them to utilise the water sources outside of their preferred temporal range. The influence of the timing of rainfall events indicates that the mean number of individual species sightings is significantly larger on days before rainfall compared to days after rainfall. The study highlights that waterdependent herbivores utilise the artificial water sources in relative proportion to their abundance in the central KNP, while water-independent herbivores are avoiding these artificial water sources. The findings of this research could be used to supplement current water provisioning guidelines and plan for water provisioning efforts in future.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science. Johannesburg, August 2016
Keywords: Water supply--South Africa--Kruger National Park; Climatic changes